Using eCognition to automatically detect and map avalanche deposits from the spring 2009 avalanche cycle in the Tatra mts., Slovakia - Frauenfelder, R.; Lato, M. J.; Biskupič, M. (International archives of the photogrammetry, remote sensing and spatial information sciences., 2015)
Here we present results from ongoing work where we apply an object oriented mapping algorithm developed in eCognition in order to automatically identify and digitally map avalanche deposits. The algorithm performance is compared with respect to a selected number of manually digitized avalanche outlines mapped by avalanche experts.